ANALISIS KETERAMPILAN MENULIS KARANGAN NARASI PADA SISWA KELAS V SD NEGERI 29 PONTIANAK KOTA - Natalia Yuliastri Winahei; Siti Halidjah; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the results of the analysis of students' skills in writing narrative essays. The method used in this study is a qualitative descriptive method. The object of this research is students' essays which are assessed from the aspects of the suitability of the title with the content, spelling writing, diction, sentence structure, inter-sentence integration, inter-paragraph alignment, overall content, and neatness. The source of the data for this research was the VC class of the 29 Pontianak City Elementary School, which amounted to 14 students. This study uses interview instruments, documentation. The results of this study indicate that the average ability to write descriptive essays is 45 in the (less) category. This is seen in terms of the percentage of students who scored in the very category of 1 person or 0.7%, the good category did not exist, the category enough was 3 people or 0.21%, the category was less than 2 people or 0.14%, the category was very less 8 people. or 0.57%. The difficulties faced by students are several aspects including the use and writing of spelling (use of capital letters, punctuation marks, writing less letters, hyphens), overall content, sentence structure, cohesiveness between paragraphs (difficulty developing paragraphs or less able to think of ideas ). Thus, it can be concluded that the ability to write narrative essays in VC class students is in the poor category because there are still some students' difficulties in writing narrative essays.